Interrelation like transparency of enamel and visual perception of the sizes of teeth (Эндодонтия Today, 2020)
In clinic of esthetic stomatology an important role is played by knowledge of optical properties of tooth and modern materials allowing to provide high quality of the performed works. Availability, a so-called, transparent layer influences visual perception of the vertical and/or horizontal sizes of tooth. Modeling of restorations assumes the choice of shades of a composite, including - transparent. The last is used at a final stage of forming of restoration for giving of individual esthetic characteristics to the last.